Real time optical-electrical characterization of PbTe thin film material for super-resolution optical memory - Lee, Hyun Seok; Lee, Taek Sung; Jeong, Jeung-hyun; Lee, Suyoun; Kim, Won Mok; Cheong, Byung-ki (KOREAN INST METALS MATERIALS, 2007)
An experimental study was conducted in an effort to elucidate the origin of the nonlinear optical properties of PbTe thin film, which previously had been demonstrated to be potentially usable for super-resolution optical memory. Using PbTe thin film device designed expressly for the experiment, transient optical transmittance and reflectance were measured together with the electrical voltage across the PbTe during pulsed irradiation with a 658 nm laser of varying power. From the measured data, the absorption coefficient was derived as well as the carrier concentration as a function of laser power, demonstrating vividly that a decrease in the absorption coefficient with increasing laser power is directly related to the increase in photo-generated carriers. The observed correlation underlying the nonlinear optical properties of PbTe may be understood in light of saturable absorption resulting from band filling by carriers photo-generated under thermal influence and is a major cause of the material's super-resolution effect.
Keywords: DATA STORAGE; RESOLUTION